2016
DOI: 10.1194/jlr.m061853
|View full text |Cite
|
Sign up to set email alerts
|

Lipotoxic brain microvascular injury is mediated by activating transcription factor 3-dependent inflammatory and oxidative stress pathways

Abstract: Vascular cognitive impairment (VCI), a form of dementia caused by cerebrovascular disease, accounts for nearly 20% of cognitive dysfunction in the United States, and yet our understanding of the cerebrovascular disease processes underlying this dysfunction remains limited (1). Our understanding of vascular pathology in atherosclerotic cardiovascular disease (ASCVD) and the systemic circulation is more advanced and suggests important avenues of investigation, given the overlap of risk factors and epidemiology b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 68 publications
1
36
0
Order By: Relevance
“…The authors concluded that heteroplasmic mtDNA variants correspond to the extent of atherosclerotic phenotypes [27]. In another study, it has been shown that ROS activated by post-prandial triglyceride lipolysis (TGRL) products (TL) increases the expression of the stress-responsive protein, activating transcription factor-3 (ATF-3), which injures human brain microvascular endothelial cells in vitro [28]. In a further study, it has been shown that ATF3-T4 predominantly regulates the TL-induced brain microvascular inflammation and TNF signaling [29].…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that heteroplasmic mtDNA variants correspond to the extent of atherosclerotic phenotypes [27]. In another study, it has been shown that ROS activated by post-prandial triglyceride lipolysis (TGRL) products (TL) increases the expression of the stress-responsive protein, activating transcription factor-3 (ATF-3), which injures human brain microvascular endothelial cells in vitro [28]. In a further study, it has been shown that ATF3-T4 predominantly regulates the TL-induced brain microvascular inflammation and TNF signaling [29].…”
Section: Discussionmentioning
confidence: 99%
“…The diseases associated with TUBB include cortical dysplasia with other brain malformations (https://www.genecards.org/). The ATF3 pathway is implicated in brain vascular damage [51]; it may be associated with amyloid deposition in AD [52]. The NOL6 is associated with ribosome biogenesis according to GeneCards database.…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of circulating TG to brain lipid uptake is unclear, as a majority of research on brain uptake of peripheral lipids have focused on non-esterified fatty acids and LPC [55]. However, further research will be needed to clarify this difference, as triacylglycerol-rich lipoproteins and their lipolysis products in high physiological concentrations are known to cause endothelial injury and dysfunction in the periphery and in the cerebral circulation [33]. …”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underpinning this association are not completely understood but broadly include capillary dysfunction; neurovascular inflammation; altered redox state and heightened oxidative stress [30–33]. With chronic ingestion of pro-inflammatory fat enriched diets, it is a reasonable proposition to suggest that changes of the brain lipidome may be realized and causally associated with some of the indicated mechanistic pathways.…”
Section: Introductionmentioning
confidence: 99%